Impact of preoperative inflammatory biomarkers on postoperative pneumonia and one-month pulmonary imaging changes after surgery for non-small cell lung cancer - Ruan, Yingding; Cao, Wenjun; Han, Jianwei; Yang, Aiming; Xu, Jincheng; Zhang, Ting (Frontiers in Oncology, 2025)
BackgroundThis study examined the effectiveness of preoperative inflammatory markers in predicting the occurrence of postoperative pneumonia (POP) and clinical outcomes based on chest computed tomography (CT) images in patients who underwent surgical resection for non-small cell lung cancer (NSCLC).MethodsThis retrospective study included NSCLC patients who underwent lung cancer surgery at The First People’s Hospital of Jiande between January 2019 and October 2023. Data on demographic characteristics, preoperative inflammatory biomarkers, surgical approach and duration, postoperative outcomes, and CT findings 1 month postoperatively were collected and analyzed. The effectiveness of preoperative inflammatory markers in predicting POP and clinical outcomes 1 month after surgical resection was assessed using propensity score matching.ResultsAmong 568 patients, 72 (12.7%) had POP. After matching, 252 patients (POP group: 66; non-POP group: 186) were included in the analysis. The systemic immune-inflammation index (SII) and platelet-to-lymphocyte ratio (PLR) were significantly higher in the POP group than in the non-POP group (433.53 vs. 323.75, P = 0.001; 126.42 vs. 103.64, P < 0.001). The length of hospital stay and the percentage of patients who improved clinically based on chest CT findings 1 month after surgery were significantly higher in the POP group than in the non-POP group (11 days vs. 9 days, P = 0.008; 77.3% vs. 59.7%, P = 0.033). Multivariate analysis showed that PLR and the lymphocyte-to-monocyte ratio (LMR) were independent predictors of POP (AUC of 0.780 and 0.730, both at P < 0.001). However, there were no significant differences in postoperative radiographic outcomes among patients stratified by risk of POP.ConclusionPLR and LMR accurately predict POP in surgical patients with NSCLC. Nonetheless, these ratios may not significantly predict radiographic outcomes 1 month after surgical resection.